“To Tannu Tuva”: On a half-forgotten book - Tatarintseva, Margarita P. (The New Research of Tuva, 2020)
The article analyses the book by V. Machavariani and S. Tretyakov titled ‘To the Tannu Tuva’, published in 1930-1931 in the genre of a travelogue, following the Tuvan trip of V. Machavariani, an official at the Communist Youth International. The book is important both for researchers and general readers, considering the lack of books about Tuva during the period of TPR, especially written for the wide audience.The article provides a brief history of the edition, including the fact why V. Machavariani had a co-author, writer S. Tretyakov. Machavariani carried out a serious mission in Tuva, strengthening the role of the Komsomol, meeting with the leadership of the party and the government of the young Republic. However, the book contained mostly his impressions of the world he saw in Tuva rather than sociopolitical events and grand changes in the life of Tuvans. The author describes nature, settlements, people, meetings and communications, conversations, and business meetings through the prism of his personal attitude. The book turned out to be a travel journal, and not a piece of socio-political propaganda as it might have been intended. Despite its entertaining content, it faced scathing criticism and was soon forgotten.The author believes this book must be republished with historians’ comments.
Keywords: Tuva; Tuvan history; “To Tannu Tuva”; V. Machavariani; S. Tretyakov; Usinsky trakt; Kyzyl; Tuvans